"It's what's behind the mask": Psychological diversity in compassionate patient care. (October 2018) - Bleiker, J.; Knapp, K.M.; Morgan-Trimmer, S.; Hopkins, S.J.
Abstract: Introduction: The Francis Report recommended an increased focus on compassion in healthcare, and recognition and non-judgmental acceptance of diversity is fundamental in compassionate patient care. The aim of this study was to achieve a wider understanding of diversity that includes individual patient needs, expectations, perceptions and feelings during diagnostic imaging. Methods: Using thirty-four semi-structured interviews with individual patients, this qualitative study explored their experiences of undergoing diagnostic radiography examinations and asked what compassionate care meant to them and how it is perceived and manifested in the brief, task-focussed and highly technical diagnostic projection imaging encounter. Data were analysed using Thematic Analysis. Results: Four key themes were identified from the analysis; these were: feelings and vulnerability; hidden emotions; professionalism and valued qualities and communication. Conclusion: Diversity is defined not only in terms of socio-cultural differences but also psychological ones, i.e. individual emotional and attitudinal characteristics, some of which may be consciously or unconsciously concealed. In order that patients are treated equitably and all of their care needs met, recommendations include a broader focus in education and training to include adapting communication skills and techniques in perception and expression of non-verbal cues. Further research into the pressures specific to the time-pressured, task-focussed, highly technical and rapid turnover environment of projection imaging radiography and how this impacts upon compassionate patient care would make a useful contribution to the field. Highlights: Diversity is a psychological as well as a socio-cultural phenomenon. The psychological aspects of diversity are less well addressed in the literature. Psychological differences are mental phenomena and can be difficult to perceive. Patients may feel inhibited from asking questions, causing uncertainty and anxiety. The term 'adapted technique' could include interpersonal and communication skills.